Investigating walkability and bikeability in compact vs. new extensions: the case of Greater Cairo - Eldeeb, Sally; Masoumi, Houshmand (Frontiers in Built Environment, 2023)
Despite the urgent need to adopt sustainable transportation methods to reduce pollution, some cities, particularly in developing countries, are still prioritizing the construction of roads for private cars. The Greater Cairo Region is experiencing increased reliance on cars, causing strain on the road network, leading to traffic congestion, decreased walkability, and social isolation, especially in gated communities. Old Cairo downtown has implemented sustainable transportation options, but more action is needed from city authorities to prioritize sustainable transportation methods for pedestrians, cyclists, and public transit users to create livable cities and promote public health. The objective of this study is to assess the walkability and bikeability of three distinct city centers: Old Cairo, which represents the historic area of the Greater Cairo Region, and the newer extensions, namely, New Cairo and 6th October City. The analysis of walkability and bikeability will be based on the Walk Score metric, while the relationship with urban form integration will be evaluated using space syntax in-depth maps. The results indicate that the walkability rates in Old Cairo downtown surpass those of the newer extensions of the Greater Cairo Region due to the compact urban fabric and highly integrated street network and activities. In conclusion, this study sheds light on the reasons for car dependency in the new extensions of Greater Cairo and emphasizes the significance of collaboration between local public transportation authorities, the Ministry of Housing, global organizations, and international agendas.